159 DSE audit – mater infirmorum hospital, belfast. (May 2019) - Cox, Brian; Thompson, Patrick; Maynard, Suzanne
Abstract : Introduction: Stress echocardiography is a well-established, functional test used in the investigation of chest pain. Its advantages are wide availability, safety and low cost. It forms a part of the ESC guideline for patients with an intermediate probability of stable coronary artery disease. It is a useful test for patients admitted with chest pain and negative cardiac biomarkers prior to discharge. Methods: The goal of this study was to investigate the rate of acute cardiac events within 2 years of a negative DSE. Data was collected from dobutamine stress echocardiograms (DSE) performed over a continuous 24 month period between February 2014 & January 2016 in the Mater Infirmorum Hospital (MIH) Cardiac Investigations Laboratory, Belfast. During DSE, an incremental dobutamine infusion protocol was used to achieve a heart rate of 85% maximum predicted. A negative result was where no areas of inducible ischaemia were demonstrated in a patient who had met their target heart rate. The data collection proforma was based upon British Society of Echocardiography recommendations. The patients' Electronic Care Record was used for data collection, which included; demographics, history of ischaemic heart disease, DSE reports, reason for referral and any cardiac events in the following two years. Results: 325 DSE's were performed during the study period: 165 patients were male and 160 were female. Mean age was 64.1 years with a range of 27–92 years. Ten of the cohort died in the follow up period but none were due to cardiac causes and were excluded from the final analysis. 29.4% of the audit population had a prior history of IHD. The majority of patients were clinic referrals (73.6%) with other referral sources being; Inpatient (12.3%), RACPC (8.9%), ED (2.1%), Other (2.7%). The indication for assessment by DSE included; chest pain (78.5%), vocational assessment (8.655), lesion assessment (3.4%), Pre-op (2.7%), and Other (5.5%). 70.5% of patients had not had a recent Exercise Stress Test. 20.9% had had an inconclusive EST. 2.8 % had a recent positive with 5.5% having had a recent negative EST. The Complications documented are shown in the table 1; The results of the DSE's are shown in Graph 1; The breakdown of the management of patients with positive DSEs (n=29) is shown in graph 2; Finally, we looked at cardiac events within 2 years in the subpopulation with a negative DSE (n=296) (table 2 ); Conclusion: No patients with a negative DSE went on to have ACS within the next 2 years; and only 1.8% went on to have coronary intervention. This suggests that a negative DSE has a good negative predictive value. We conclude that DSE is a very useful test in the investigation of cardiac chest pain. In addition it is a safe test with 93% experiencing no complications. In the future it would be useful to update this study with larger patient numbers and to comparing DSE results with other functional tests available. Conflict of Interest: n/a